2005
DOI: 10.1002/hec.1053
|View full text |Cite
|
Sign up to set email alerts
|

Health status and labour force participation: evidence from Australia

Abstract: This paper examines the effect of health on labour force participation using the Household, Income and Labour Dynamics in Australia (HILDA) Survey. The potential endogeneity of health, especially self-assessed health, in the labour force participation equation is addressed by estimating the health equation and the labour force participation equation simultaneously. Taking into account the correlation between the error terms in the two equations, the estimation is conducted separately for males aged 15-49, male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
232
1
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(284 citation statements)
references
References 26 publications
(56 reference statements)
21
232
1
17
Order By: Relevance
“…Deteriorating health and the presence of chronic disease and associated comorbidities, together with symptoms such as severe, frequent and chronic pain would be expected to be associated with reduced labor supply 25 . There is ample empirical data to support this expectation, notably in respect of chronic disease states 26,27 . Breivik et al, in their pan-European pain assessment report that one in four respondents had indicated that pain impacted their employment status, 19% had lost their job because of pain, 16% had changed their job responsibilities and 13% had changed jobs entirely 4 .…”
Section: Labor Force Participationmentioning
confidence: 98%
“…Deteriorating health and the presence of chronic disease and associated comorbidities, together with symptoms such as severe, frequent and chronic pain would be expected to be associated with reduced labor supply 25 . There is ample empirical data to support this expectation, notably in respect of chronic disease states 26,27 . Breivik et al, in their pan-European pain assessment report that one in four respondents had indicated that pain impacted their employment status, 19% had lost their job because of pain, 16% had changed their job responsibilities and 13% had changed jobs entirely 4 .…”
Section: Labor Force Participationmentioning
confidence: 98%
“…Additionally, unemployment is associated with unhealthy behaviors such as increased alcohol and tobacco consumption and decreased physical activity [9,16,17]. Studies have also demonstrated a positive correlation between employment and better health, improved self-confidence, self-esteem, and happiness [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also reported that workers with a poor health are more likely to become unemployed (4,(7)(8)(9)(10)(11) and, to a smaller extent, to retire before the statutory retirement age (4,11,12).…”
mentioning
confidence: 99%